Anthropometry of Muscle Mass: The Relationship Between Risk and Nutritional Status and Functionality in the Elderly - Medim, Letícia Thalia; Ferrari, Daiane; Costodio, Adriane Rosa; Schuch, Natielen Jacques; Santos, Pâmela Antoniazzi dos; Siviero, Josiane; Margutti, Karen Mello de Mattos (O Mundo da Saúde, 2023)
Aging modifies the body composition and physiology of individuals, influencing the decrease in body mass and nutritional status. This study aims to analyze the association between anthropometric indicators of muscle mass assessment with nutritional risk and functional deficit in the elderly. This is a cross-sectional study, with community-dwelling elderly (≥ 60 years old) assisted in primary care centers in the city of Doutor Ricardo, RS. The analyzed variables were: sociodemographic data; lifestyle; chronic noncommunicable diseases; nutritional risk; nutritional status; muscle mass; skeletal muscle mass index; calf circumference; corrected arm muscle area; adductor pollicis muscle thickness; adductor muscle index; and functionality. For statistical analysis, P <0.05 was used. Forty-four elderly people with a mean age of 71.27±8.57 years were evaluated, 68.2% of whom were female (N= 30). Men had higher mean muscle mass (P <0.001) and skeletal muscle mass index (P <0.001). Higher percentages of inadequate calf circumference and skeletal muscle mass index were associated with the risk of malnutrition and low weight (P <0.001). The relationships found with the indicators for assessing muscle mass, skeletal muscle mass index and calf circumference with nutritional risk and inadequate nutritional status point to the relevance of using these indicators in clinical practice.